2015
DOI: 10.1007/s11427-014-4768-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insect-resistant GM rice on pesticide use and farmers’ health in China

Abstract: The economic benefits of insect-resistant genetically modified (GM) crops have been well documented, but the impact of such crops and the consequent reduction in pesticide use on farmers' health remains largely unknown. Through the analysis of the data collected from the physical examination from farmers in China, we show that GM rice significantly reduces pesticide use and the resultant not only visible but also invisible adverse effects on farmers' neurological, hematological, and electrolyte system. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…During the past 20 years, numerous insect resistance genes have been identified, some of which have anti-lepidopteron activity ( cry1Aa, cry1Ab, cry1Ac, cry1Ab/Ac, cry1C, cry2A , and CpT1 ), whereas others exhibit anti-helipterum activity ( Galanthus nivalis agglutinin, gna , and Pinellia ternata agglutinin, pta ). These genes have been introduced into rice to develop insect-resistant transgenic lines (Shu et al, 1998, 2000; Tan et al, 2011; Wang et al, 2012a,b; Jiang et al, 2013b; Jian et al, 2014). Currently, most insect-resistant transgenic rice lines in China are in the field trial stage (Tang et al, 2006; Wang et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…During the past 20 years, numerous insect resistance genes have been identified, some of which have anti-lepidopteron activity ( cry1Aa, cry1Ab, cry1Ac, cry1Ab/Ac, cry1C, cry2A , and CpT1 ), whereas others exhibit anti-helipterum activity ( Galanthus nivalis agglutinin, gna , and Pinellia ternata agglutinin, pta ). These genes have been introduced into rice to develop insect-resistant transgenic lines (Shu et al, 1998, 2000; Tan et al, 2011; Wang et al, 2012a,b; Jiang et al, 2013b; Jian et al, 2014). Currently, most insect-resistant transgenic rice lines in China are in the field trial stage (Tang et al, 2006; Wang et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a 2‐year field study with Bt Shanyou 63 in Wuhan (Wang et al ., ) suggested that planting of Bt rice can reduce pesticide spraying by 50–60% compared to non ‐Bt rice, and that Bt rice could increase rice yield by 60–65% compared with non‐ Bt rice when no insecticide was applied. A recent study of farmers' physical examination was conducted to estimate the invisible health impact of pesticide reduction through the adoption of Bt rice on farmers' health, and the results suggested that Bt rice significantly reduced the pesticide use and, as a consequence, improved the health of farmers in China (Huang et al ., ). Results of these studies indicated that use of transgenic Bt rice benefits the environment, increases farmers' income and improves their health.…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
“…; Qiao ), including the farmers themselves (Huang et al. , ). GE crops have been adopted faster than any other agricultural advance in the history of humanity (Alberts et al.…”
Section: Adoption Of Crop Biotechnologymentioning
confidence: 99%
“…However, many weed species recently have evolved resistance to glyphosate and other overused herbicides that are required by these GE crops, such that the long-term sustainability of facilitating low-and no-till agriculture is not certain (Mortensen et al 2012). Production of Bt cotton and rice increases yield (9% in the case of cotton - Huang et al 2003; 9-29% for rice -reviewed by Chen et al 2011), whereas less pesticide is sprayed on the field, decreasing impacts on nontarget organisms (Huang et al 2003;Li et al 2015;Qiao 2015), including the farmers themselves (Huang et al 2015a(Huang et al , 2015b. GE crops have been adopted faster than any other agricultural advance in the history of humanity (Alberts et al 2013).…”
Section: Adoption Of Crop Biotechnologymentioning
confidence: 99%